Peran Pancasila Sebagai Fondasi Identitas Nasional Indonesia Dalam Menjawab Tantangan Globalisasi - Sikana, Arina Mana; Dzulqarnain, Abdullah Alif; Syafitri, Falya Rahmatika; Faizin, Moh. (Universitas Cokroaminoto Yogyakarta, 2025)
Currently, Pancasila is facing various challenges due to the impact of globalization on the Indonesian nation. This discussion focuses on the negative impact of globalization that threatens the existence of Pancasila as a national identity. As the next generation of the nation, it is essential for young people to understand and properly implement Pancasila in their lives so that it does not become lost amid an increasingly advanced civilization. This article was written to understand the importance of Pancasila’s role in responding to the challenges of globalization. The research methodology employed was analyzing existing sources such as journals, articles, and books. The author explains how Pancasila serves as a national identity, emphasizing the importance for the current generation to practice each principle of Pancasila and understand, its vital role for the Indonesian nation, especially in the era of globalization. This is because various problems arising from globalization threaten Pancasila and its existence as the foundation of national identity. The role of Pancasila is becoming increasingly challenging due to the behavior of the younger generation, which is increasingly perceived as not aligning with the principles of Pancasila. Moral degradation is occurring, and Nationalism is beginning to fade in the souls of the current younger generation. If this continues, Indonesia’s national identity could be lost and which would have a negative impact on the future of the Indonesian nation.